Identifying the developmental stages and optimizing the sample preparation for anatomical study of Orthosiphon stamineus - Manaf Almatar and Zaidah Rahmat (Journal of Applied Pharmaceutical Science, 2014)
This study focuses on the characterization of morphological and anatomical traits of Orthosiphon stamineus which belongs to the Lamiaceae family. Orthosiphon stamineus, better known as “Misai Kucing” or “cats whiskers” by the locals, contained active phenolics compounds such as flavanoids. Despite its wide usage as a medicinal plant, information regarding Orthosiphon stamineus specific developmental stages is relatively scarce. Furthermore, to date, no anatomical data of this plant is available. Therefore, this study aims to systematically identify the developmental stages and its anatomy which may provide more insight to its medical application. The result showed some distinct morphological and anatomical characteristics. In the morphological study, it was observed that Orthosiphon stamineus is a herbal shrub with well-developed creeping rootstock. The leaves are simple, green, and arranged in opposite pairs. The stem is approximately 54 cm in height at the oldest stage (62-64 days). In order to proceed with the anatomical study of Orthosiphon stamineus, the cross sections of different developmental stages of leaves and stems were examined. Several critical steps prior to viewing the prepared slides, which include dehydration, sectioning and staining, were optimized accordingly.
Keywords: Orthosiphon stamineus, Morphology, Anatomy, Lamiaceae.